Characterization and functional potential of tofu whey wastewater as a food ingredient : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Auckland, New Zealand - Jitpungtum, Roongchai (Massey University, 2025)
Tofu whey, a liquid by-product of tofu production, is often discarded as wastewater, leading to environmental and economic concerns. However, its nutritional composition and bioactive properties suggest potential applications as a functional food ingredient. This study aims to characterize the physical and chemical properties of tofu whey liquid (TWL) and tofu whey powder (TWP), evaluate their functional properties, including foaming and emulsifying abilities, and investigate their bioactive properties. Additionally, their potential as an egg white substitute in meringue formulations was assessed. TWL is the liquid waste by-product generated during tofu-making and TWP is the powder obtained by removing most of the moisture from TWL. Chemical composition analysis revealed that TWL contained 97.34 ± 0.23% moisture, 0.38 ± 0.05% crude protein, 0.10 ± 0.06% fat, 0.43 ± 0.05% ash and 1.76 ± 0.23% carbohydrates, while TWP had 5.23 ± 1.04% moisture, 15.08 ± 0.35% crude protein, 1.54 ± 0.29% fat, 15.09 ± 1.74% ash and 62.88 ± 2.27% carbohydrates. The primary sugar identified was sucrose, and the proteins were mainly degraded subunits of glycinin and conglycinin. Mineral analysis showed significant levels of copper, chloride, iron, magnesium and potassium. Functionality testing demonstrated that TWL exhibited limited foaming properties, while TWP showed improved foam stability at a 10% concentration, maintaining over 50% stability after 30 minutes. When adjusted to pH 4 from pH 5.8, foam stability further improved, exceeding 60%. Emulsification studies indicated that TWL had poor stability at higher oil concentrations (20%) but performed better at lower oil concentrations (5%). In contrast, TWP exhibited enhanced emulsifying properties across various oil concentrations, particularly at pH 2 and pH 7–9, likely due to improved zeta potential. The addition of 500 mM NaCl further increased emulsion stability by promoting Na⁺-water interactions, enhancing electrostatic repulsion. Th bioactive properties of TWL and TWP were also analysed, including their antioxidant, antimicrobial, and anti-browning activities. The results indicated that both TWL and TWP contained decent levels of total phenolics, flavonoids, and saponins. These bioactive compounds suggest potential applications in extending food shelf life and enhancing overall product stability. As an egg white substitute in meringue, TWL and TWP produced mixed results. The best performance showing similar texture and rheological to egg white, was observed when TWL or TWP was incorporated with egg white, with minimal impact on meringue texture. Batter made with TWP alone showed no significant differences in density and φ (air incorporation) compared to egg whites, whereas TWL resulted in higher density and lower φ, correlating with increased batter viscosity. Overall, these findings highlight the potential of TWP as a sustainable functional ingredient with foaming, emulsifying, antioxidant, antimicrobial, and anti-browning properties. Future studies should explore further applications in food formulations and optimize processing conditions to enhance its bioactive and functional properties in various food systems.
Figures are reproduced with permission.
Keywords: 300607 Food technology